Reflexões em torno do paradoxo político de Paul Ricoeur - Costa, Mirian Gado Fernandes (2008)
Paul Ricoeur was concerned, in his political essays, with a philosophy of action linked to the willingness of human coexistence. In order to understand Politics as an activity based on coexistence, we should recognize concepts such as power, sovereignty, violence, as permanent features in the task of stabilization of life in common. Thus, we should revisit some philosophical works that illustrates this unique capacity of men. This work discusses Paul Ricoeur s political paradox concept, which was first brought to light in 1957, in the article he wrote analyzing the Hungarian Revolution. Focusing on Ricoeur s work, this text intends to clarify the political paradox concept, as well as to explicit political power problems such as its relative autonomy with respect to social-economic relations. The Hungarian events illustrate such problems, but this work also demonstrates how Ricoeur s analyses unfolded into a universal reflection about the political realm. Ricoeur discussed some of Hannah Arendt s papers; according to the later, Politics is the source of meaning for human life and a long-term political project is the only possibility of historical immortality for us, mortals. Some of these discussions brought up at the end of this dissertation, aim to shed light on the reflection about the political paradox and the problematic of power